A numerical technique to study arbitrary shaped cracks growing in notched elements. (1st January 2002) - Biancolini, M.E.; Brutti, C.
In this paper, a numerical technique is exposed to study the fatigue life of notched elements with arbitrary shaped cracks. In structural design, one of the most important activities is to evaluate the life under fatigue load. Recently, many research efforts were devoted to define reliable procedures able to estimate initiation and growth of cracks based on fracture mechanics. In order to obtain this result, it is necessary to study how cracks initiate, grow and propagate and to implement the theoretical results in a numerically reliable, low cost procedure. Extending the results obtains previously by the authors, this paper exposes a numerical technique able to perform the crack growth analysis of plane defects of arbitrary shape in notched element taking into account the elastic-plastic crack growth and the change of crack shape during propagation. The method exposed by Lin and Smith [7-11] is modified and improved in order to follow the evolution of the crack shape and the model proposed by Ahmad and Yates [17] is used to take into account the plasticity effects. A fully automated procedure is presented based on a step-by-step re-meshing tool. A details 3-D FEM model is prepared for each step in order to evaluate driving force along crack length, growing rate is calculated locally by means of SIF and Paris law in elastic region and by an elastic-plastic law if the crack segment lies in a region influenced by plasticity effects. Internal and external defects of various shape are easy handled for different element geometry including notched round bar, plates and plates with hole. Some examples are exposed, showing a good agreement with literature experimental data.